The relevance of physical characterisation in the evaluation of the performance of allografts - Judas, F (2002)
The present work compares bone allografts with synthetic hydroxyapatite regarding density, porosity, pore size distribution and phase identification. The measurement of these parameters enables a more complete knowledge of the grafts structural properties, which necessarily leads to a better selection of the most appropriate bone substitutes.